Developing practical climate adaptation and mitigation toolkits for Canadian forest-based communities: a systematic review - Antwi, Effah Kwabena; Darko, Akua Nyamekye; Boakye-Danquah, John; Fraser-Reid, Erin C.; Macdonald, Heather; Yohuno (Apronti), Priscilla Toloo (Frontiers in Climate, 2025)
The effects of climate change events such as wildfires, storms, flooding, and pest outbreaks remain a constant threat to the health of Canadian forests. Consequently, adaptation and mitigation actions are necessary to reduce the effects and impacts of climate change and prevent further deterioration of forest health. Using a climate change toolkit is a common way for forest practitioners to understand their climate risks, develop locally relevant adaptation and mitigation options, and drive the implementation of strategies to improve forest resilience. In this review paper, we examine how climate change adaptation and mitigation toolkits have been developed in the Canadian forest sector, the challenges that were encountered, and if and how Indigenous and local knowledge were incorporated into the process. Our results show that toolkits developed holistically and comprehensively provide a good foundation for implementing long-term impactful climate action. Achieving this requires a broad understanding and mapping of climate issues, implementation options, as well as best practices for monitoring and evaluation of action plans. If developed appropriately, toolkits can provide flexible pathways that are tailored to local changing climatic patterns, events, and impacts within specific contexts or sectors, ultimately improving forest resilience in the face of climate change.